La posibilidad redentora del lenguaje del «nombre propio» en Rosenzweig al «decir tú » en Buber - Torres Brizuela, Juan Facundo (2021)
Fil: Torres Brizuela, Juan Facundo. Pontificia Universidad Católica Argentina; Argentina